TINGKAT PENGETAHUAN TENTANG TB PARU MEMPENGARUHI PENGGUNAAN MASKER DI RUANG PARU RUMKITAL Dr. RAMELAN SURABAYA - Nur Wachida Novita; Christina Yuliastuti; Siti Narsih (Universitas Nahdlatul Ulama Surabaya, 2014)
Number of patients with pulmonary TB increased annually in Surabaya, on of the measures to prevent TB infections is by using a mask. In TB care room a lot of visitors (family) who did not wear a mask. The purpose of this study to determine the relationship of the level of knowledge with the use of masks to visitors (family).This study used correlational analytic designwith cross sectional approach. independent variable in the study is the level of knowledge about Tuberculose anddependent variable is the use of masks. Samples were taken by using purposive sampling technique earned by 28 respondents visitors in Pulmonary Wards,Dr. Ramelan Navy Hospital, Surabaya, date 11 – 20 June 2013. Data collection was undertaken using questionnaire about Pulmonary Tuberculose and observation sheet of the use of mask. Data were analyzed with Spearman's Rho test with a significance level Corellation ρ <0.05.Results showed that the level of knowledge about Tuberculose less 14 respondents (50%) and 16 respondents (57.1%) did not wear a mask. Spearman's Rho test showed that there is a relationship between the level of knowledge about Pulmonary Tuberculosewith the use of masks in in Pulmonary Wards,Dr. Ramelan Navy Hospital, Surabaya (ρ = 0.000).